Self-Reported Knee Pain Does Not Impact Physical Training Negatively in Conscripts. Issue 7 (20th February 2020) - Rips, Leho; Rahu, Madis; Kuik, Rein; Varblane, Ahti; Olveti, Indrek; Ööpik, Vahur; Mölder, Hanno; Timpmann, Saima; Tammaru, Marika; Toom, Alar; Kartus, Jüri-Toomas; Gapeyeva, Helena
Abstract: Introduction: Despite the great number of investigations on the effects of injuries during military service, there is limited information available on the use of self-reported instruments. This study evaluated self-reported knee pain (KP) and its effect on physical performance during military service in the Estonian Defense Forces. Material and Methods: Ninety-five male conscripts aged 19–25 years were divided into two study groups based on the occurrence of KP or not. Self-reported KP and function according to the Knee Injury and Osteoarthritis Outcome Score (KOOS) were measured. Physical fitness level was scored using the Army Physical Fitness Test (APFT). KOOS and APFT were measured in the beginning and at the end of the 6-month period of military service. Results: Significant differences in favor of the group without KP ( P < 0.001) were found for all subgroups of the KOOS. In spite of KP, the physical condition improved significantly ( P < 0.001) in both study groups as measured with both the APFT test (22.2% increase) and running time (10.3% decrease). Conclusion: In conclusion, self-reported KP and limited function according to KOOS did not hinder the improvement of physical condition and running speed as assessed by APFT in Estonian conscripts.